2021
DOI: 10.2147/jpr.s304805
|View full text |Cite
|
Sign up to set email alerts
|

Nonmedical Use of Xtampza® ER and Other Oxycodone Medications in Adults Evaluated for Substance Abuse Treatment: Real-World Data from the Addiction Severity Index-Multimedia Version (ASI-MV®)

Abstract: Purpose The purpose of this study was to evaluate real-world data related to past 30-day nonmedical use (NMU) and routes of administration of Xtampza ® ER and comparator oxycodone medications in the US as captured within the Addiction Severity Index-Multimedia Version ® (ASI-MV ® ). Methods Data were collected from July 2016 through December 2019 from 647 centers located in 44 states using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
(26 reference statements)
0
4
0
Order By: Relevance
“…Further, Xtampza ER had lower rates of non-oral manipulation, including insufflation and injection, than did the other ER ADF oxycodone group. 11 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, Xtampza ER had lower rates of non-oral manipulation, including insufflation and injection, than did the other ER ADF oxycodone group. 11 …”
Section: Discussionmentioning
confidence: 99%
“…The large national studies demonstrated differences in misuse, abuse, and diversion rates among ADF ER opioids. 11 , 12 Still, the economic implications of these findings have not been further elaborated. There is also a lack of studies directly comparing different formulations of the same medication, and this may be the most accurate way to measure the impact of ADF formulations.…”
Section: Introductionmentioning
confidence: 99%
“… Green JL et al J Pain Res . 2021 59 Rates of nonmedical use (deviation from legitimate medical use) of Xtampza ER were lower than other oxycodone ER (eg, OxyContin) and IR products. Severtson SG et al Pain Med .…”
Section: Manipulation Methodsmentioning
confidence: 99%
“…An analysis of the Addiction Severity Index-Multimedia Version found that Xtampza ER had significantly lower rates of nonmedical use and nonoral nonmedical use than OxyContin and non-ADF oxycodone IR products in individuals seeking substance abuse treatment. 59 A study evaluating the RADARS system found low rates of abuse/misuse (composite endpoint of cases by combining 3 exposure categories: intentional abuse, intentional misuse, and intentional unknown exposures as defined in the annual report of the National Poison Data System) and diversion of Xtampza ER compared with other prescription opioid analgesics. 60 Moreover, abuse and misuse did not increase for 3 years (July 1, 2016, through June 30, 2019) after initial marketing of Xtampza ER into the US market.…”
Section: Manipulation Methodsmentioning
confidence: 99%